Psychosocial factors for risk and protection to child malnutrition in mothers of malnourished and eutrophic children: the role of maternal mental health - Silveira, Flávia Cristina Pereira [UNESP]; Perosa, Gimol Benzaquen [UNESP]; Carvalhaes, Maria Antonieta de Barros Leite [UNESP] (My University, 2012)
In this study, the relationship between child malnutrition, depression, anxiety and other maternal socio-demographic variables was investigated in mothers of malnourished (MD) and eutrophic (ME) children. The causes attributed by mothers to malnutrition were also studied. Ten mothers from each group, with children aged from 11 months to three years and who were users of primary health care units, participated in the study. They answered Beck depression and anxiety inventory, a questionnaire on vital events and an open question concerning the causes of malnutrition. The evaluation instruments were corrected according to proper guidelines and comparative analyses between the groups were performed. The answers to the open question were qualitatively evaluated, submitted to content analysis. The mothers in the two groups were nearly 30 years old or older. They had a steady partner and were subject to very similar life conditions. They had attended school for 5.5 years and were housewives or worked in low-income jobs. Concerning mental health indicators, a significantly larger number of mothers in the MM group showed depression indicators when compared to mothers in the EM group. Most mothers attributed malnutrition to biological factors or to the lack of maternal care, with more moralist statements in the EM group, and statements filled with guilt in MM. Results suggest that in order to fight malnutrition, in addition to nutritional interventions, it is necessary to heed attention to maternal socio-emotional issues.
Keywords: Anxiety; Depression; Malnutrition; Mental health